BIAYA PRODUKSI ALAT MUAT DAN ALAT ANGKUT PADA KEGIATAN PENGUPASAN OVERBURDEN PENAMBANGAN BATUBARA DI PT. KARBINDO ABESYAPRADHI - Toni Mayyondra; Murad Murad; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2015)
PT. Karbindo Abesyapradhi is one of the coal mines located in West Sumatera province Sijunjung. In mining PT. Karbindo Abesyapradhi in cooperation with PT. Pasura Bina Mine as a sub contractor who is a subsidiary of Srikandi Group.Based on observations in stripping overburden at PT. Karbindo Abesyapradhi, it was found that the production activities of overburden is not optimal. This is caused by equipment that works on the field non optimal when used, which is visible from the unloading tool is waiting on the field.Actually total unloading production is 104,910 BCM/month, and conveyances 84,590 BCM/month, it caused not achieving the target production of overburden that has been planned not reached. After analysis it is found that the cause of low production work efficiency is low and lack of transport in use. By increasing the efficiency of work and made additional conveyance, then obtained a total production of 131,090 BCM tool loading / month and conveyance 123,436 BCM/month.From the results of the calculation, the cost of production and the means of conveyance and unloading tool to strip overburden before it is analyzed is Rp.2,511,980,033/month or Rp.29,696/BCM, and having analyzed the cost of production tools and conveyances fit into Rp.3,022,347,665/month or Rp.24,485/BCM, so to strip the overburden in accordance with the planned production target required fee of Rp.2,938,200,000